Approaches to the study of the development of Spanish among indigenous schoolchildren in the school of Lima - Meneses T., Norma I. (2000)
The situation of education in our country evidences a multifaceted problem. One of these facets, perhaps the most important and at the same time the least attended, is the linguistic aspect.